Effect of occupational exposure to antineoplastic drugs on DNA damage in nurses: a cross-sectional study. Issue 4 (30th December 2021) - Huang, Xiaohong; Gao, Chaoxian; Cai, Wenzhi; Tao, Yanling; Zhong, Xiao; Liu, Haiying; Hong, Xiaodan; Ding, Xiaorong; Lu, Hong; Lai, Wenjuan; Yi, Xiaoqing; Gu, Yeqing
Abstract : Background: Although the therapeutic effect of antineoplastic drugs is incontestable, these agents can also potentially act as carcinogens, mutagens and/or teratogens in people. The aim of this study was to assess the effect of occupational exposure to antineoplastic drugs on DNA damage, assessed by the comet assay and cytokinesis-block micronucleus (CBMN) assay, in nurses. Methods: The cross-sectional study enrolled 305 nursing staff members from 7 public hospitals in Shenzhen who handled antineoplastic drugs, and 150 healthy nursing staff members who were not exposed to antineoplastic drugs as the control group. DNA damage was assessed by the comet and CBMN assay. Multiple linear regressions and logistic regressions models were used to analyse the effect of occupational exposure to antineoplastic drugs on DNA damage. Results: After adjustment for confounding factors, compared with non-exposure to antineoplastic drugs, exposure to antineoplastic drugs was positively related to tail moment, olive moment, tail length and tail DNA per cent, and adjusted β or OR (95% CI) was 0.17 (0.08 to 0.26), 0.18 (0.10 to 0.27), 1.03 (0.47 to 1.60) and 1.16 (1.04 to 1.29) (all p<0.05). Moreover, similar significant relationships were observed for the biomarkers of the CBMN assay. Additionally, other than age, there was no interaction between antineoplastic drug exposure and other variables for the levels of biomarkers of the CBMN assay and the comet assay. Conclusions: The present results showed that exposure to antineoplastic drugs was positively related to the risk of DNA damage in nurses. The results imply that occupational exposure to antineoplastic agents is an important global public health problem that requires urgent attention.